Kebutuhan Pelatihan Pengembangan Keprofesian Berkelanjutan Guru Sekolah Dasar - Hamid, Abd. (Indonesian Journal of Educational Studies, 2016)
Continuous professional development is conducted Â in accordance with the needs of teachers to achieve the standard of professional competence which also has implications for credit scoring for promotion / functional. Research was to understand the form of the training needs of sustainable professional development (PKB) on elementary school teachers in Gowa. Type descriptive qualitative research. Research subjects in primary school teachers in Gowa district, amounting to 35 people. The results showed the form of continuous professional development training needs (PKB) needed elementary school teacher in Gowa is is a selfdevelopment training, on a very important category. Because the primary school teachers aware of the importance of self-development should start from the teachers themselves.